Current status and development direction of immunomodulatory therapy for intervertebral disk degeneration - Gao, Yanbing; Chen, Xiyue; Zheng, Guan; Lin, Maoqiang; Zhou, Haiyu; Zhang, Xiaobo (Frontiers in Medicine, 2023)
Intervertebral disc (IVD) degeneration (IVDD) is a main factor in lower back pain, and immunomodulation plays a vital role in disease progression. The IVD is an immune privileged organ, and immunosuppressive molecules in tissues reduce immune cell (mainly monocytes/macrophages and mast cells) infiltration, and these cells can release proinflammatory cytokines and chemokines, disrupting the IVD microenvironment and leading to disease progression. Improving the inflammatory microenvironment in the IVD through immunomodulation during IVDD may be a promising therapeutic strategy. This article reviews the normal physiology of the IVD and its degenerative mechanisms, focusing on IVDD-related immunomodulation, including innate immune responses involving Toll-like receptors, NOD-like receptors and the complement system and adaptive immune responses that regulate cellular and humoral immunity, as well as IVDD-associated immunomodulatory therapies, which mainly include mesenchymal stem cell therapies, small molecule therapies, growth factor therapies, scaffolds, and gene therapy, to provide new strategies for the treatment of IVDD.